Primary Trophoblast Cultures: Characterization of HLA Profiles and Immune Cell Interactions - Eikmans, Michael; van der Keur, Carin; Anholts, Jacqueline D. H.; Drabbels, Jos J. M.; van Beelen, Els; de Sousa Lopes, Susana M. Chuva; van der Hoorn, Marie-Louise (Frontiers in Immunology, 2022)
Introduction: Trophoblasts are essential in maternal-fetal interaction during pregnancy. The goal was to study HLA profiles of primary trophoblasts derived from placentas, and to investigate their usefulness in studying interaction with immune cells. Methods: After enzymatic digestion of first-trimester placental tissue from seven donors (6-9 weeks gestation) and trophoblast enrichment, we cultured cytotrophoblasts (CTB) in stem cell medium. CTB were differentiated into EVT in a Matrigel-containing medium. Expression of classical HLA molecules and of HLA-G was studied by flow cytometry, qPCR, and ELISA, in comparison to secondary trophoblast cell lines JAR and JEG-3. Lymphocytes were studied during co-culturing with EVT. Results: The trophoblasts could be easily maintained for several passages and were selective in expressing HLA-C, but not HLA-A and HLA-B. Upon differentiation to EVT, cells showed increasing expression of total HLA-G, an increasing proportion of HLA-G1 over G2- and G3 isoforms, and elevated excretion of soluble HLA-G. These features were distinct from those of the secondary trophoblast cell lines. TNF-α and IL-8 represented the most abundantly secreted cytokines by CTB, but their levels were minimal in EVT cultures. As proof of principle we showed that EVT affect lymphocytes in three-day co-cultures (n=4) by decreasing activation marker HLA-DR. Conclusion: We verified the possibility of placenta-derived trophoblasts from first-term placentas, and their capability of differentiating to HLA-G expressing EVT. This culture model better represents the in-vivo situation than previously studied secondary trophoblast cell lines and enables mechanistic studies of fetal-maternal interactions.